Spectroscopy of charmed sigma and lambda baryons in lattice quantum chromodynamics - Ilgın, Fatih (My University, 2017)
Quantum Chromodynamics (QCD) is a theory of strong forces. In low- energy regions we need non- perturbative methods to study hadron properties. Lattice QCD is a numerical and non-perturbative approach to QCD. This method is formulated on a 4-D discretized Euclidean space-time and starts directly from the QCD Lagrangian. In this thesis, we have used 32 ^3x 64 and 2+1 flavor lattices to calculate the effective mass values for charmed Lambda and Sigma baryons which are in agreement with experimental result and with those of other collaborations.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2017
Keywords: Quantum chromodynamics; Lattice qed; Hadron spectroscopy